Tunable electrode architectures for La0.8Sr0.2Fe1-xTixO3-δ based Symmetrical Solid Oxide Fuel Cells. - Zamudio-García, Javier; Porras-Vázquez, José Manuel; Losilla, Enrique R.; Marrero-López, David (My University, 2021)
The efficiency of SOCF electrodes can be improved by optimizing the microstructure from alternative preparation methods, such as infiltration and nanostructured electrodes deposited at low temperature. Recent studies have demonstrated that spray-pyrolysis deposition is a versatile method to obtain nanostructured electrodes with improved performance in comparison with conventional electrodes prepared at high sintering temperatures. Among the different electrodes studied in the last few year, titanium-doped ferrites are one of the most promising because of their high redox stability and great electrochemical performance in both oxidizing and reducing conditions2,3. In this work, (La0.8Sr0.2)0.95Fe1-xTixO3-δ (x=0.2, 0.4) perovskites, hereafter labelled as LSFT02 and LSFT04, respectively, with different architectures were obtained by spray-pyrolysis deposition and they were tested as symmetrical electrodes for solid oxide fuel cell (SSOFC).
Comunicación Oral
Keywords: Baterías de acumuladores; Simmetrical Solid Oxide Fuel Cells; Nanostructured electrodes; Spray-pyrolysis